2018
DOI: 10.1142/s0219455418500025
|View full text |Cite
|
Sign up to set email alerts
|

Resonance of a Quasi-Zero Stiffness Vibration System Under Base Excitation with Load Mismatch

Abstract: The primary resonance and 1/3 subharmonic resonance of a quasi-zero stiffness (QZS) vibration system under base excitation with load mismatch are studied in this research. The incremental harmonic balance (IHB) method is applied to obtain highly accurate solutions involving more dynamic behaviors. The effect of the offset displacement mainly caused by overloading on the primary resonance and displacement transmissibility is investigated. The results indicate that the system exhibits a softening characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Cheng et al [36] found that the nonlinear damping could eliminate the unbounded response of the displacement transmissibility. Cheng et al [37] considered the load mismatch, and found that the QZS isolator still outperformed the equivalent linear isolator. Wang et al [38] connected the upper platform of the isolator with an inerter to enhance the performance.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [36] found that the nonlinear damping could eliminate the unbounded response of the displacement transmissibility. Cheng et al [37] considered the load mismatch, and found that the QZS isolator still outperformed the equivalent linear isolator. Wang et al [38] connected the upper platform of the isolator with an inerter to enhance the performance.…”
Section: Introductionmentioning
confidence: 99%
“…This isolator possesses high-static-low-dynamic stiffness so that it can maintain the load-bearing capacity with a small static displacement and achieve a lower natural frequency to enlarge frequency ranges of vibration isolation. But, it should be noted that isolators with QZS are very sensitive facilities and if something occurs to cause deviation of its characteristic parameters (e.g., mismatch of the load and negative stiffness parameters) and/or change in the non-linearity properties of its forces (e.g., destruction of the symmetry), then the isolation performance will change dramatically [19][20][21][22]. This situation is particularly true when the amplitude of excitation is not relatively small, and the isolator is exposed to a sustained excitation.…”
Section: Introductionmentioning
confidence: 99%